2011
DOI: 10.1007/s10165-011-0504-x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory involvement in IgG4-related Mikulicz’s disease

Abstract: 'Immunoglobulin G4 (IgG4)-related disease' is a new clinical concept of multi-organ diseases, with Mikulicz's disease (MD) being a clinical phenotype of IgG4-related disease. To clarify the clinical characteristics of respiratory involvement associated with IgG4-related MD, we retrospectively assessed 25 patients with MD, 11 (44%) of whom had allergic symptoms, and 7 (28%) of whom complained of respiratory problems. Thirteen patients (52%) presented with pulmonary and/or mediastinal lesions (P-MD) on chest com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…IgG4-RD has been found to affect the pancreas [9, 10], bile duct [10, 11], lacrimal glands [10, 12], salivary glands [10, 12], central nervous system [10, 13, 14], thyroid [10, 15, 16], lungs [10, 17, 18], liver [10, 19, 20], gastrointestinal tract [10, 21–24], kidney [10, 25, 26], prostate [10, 27, 28], retroperitoneum [10, 29], arteries [10, 30], lymph nodes [10, 31], skin [10, 32], and breast [10, 33]. However, before the disease was identified, each organ lesion was described independently.…”
Section: The History Of Igg4-related Disease: Before and After Discovmentioning
confidence: 99%
“…IgG4-RD has been found to affect the pancreas [9, 10], bile duct [10, 11], lacrimal glands [10, 12], salivary glands [10, 12], central nervous system [10, 13, 14], thyroid [10, 15, 16], lungs [10, 17, 18], liver [10, 19, 20], gastrointestinal tract [10, 21–24], kidney [10, 25, 26], prostate [10, 27, 28], retroperitoneum [10, 29], arteries [10, 30], lymph nodes [10, 31], skin [10, 32], and breast [10, 33]. However, before the disease was identified, each organ lesion was described independently.…”
Section: The History Of Igg4-related Disease: Before and After Discovmentioning
confidence: 99%
“…Not all IgG 4 -RD patients' serum IgG 4 levels are elevated,7 and up to 40% of patients with biopsy-proven IgG 4 -RD had normal serum IgG 4 levels 8. However, some reports showed that serum IgG 4 levels in patients with multiple organ involvement were higher,9 10 and correlated with disease activity 11. Amid the controversy in IgG 4 -RD, the clinical interpretation of serum IgG 4 concentrations in IgG 4 -ROD has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…IgG4-related pulmonary disease (IgG4-PD) often develops in males aged about 60 years. The frequency of allergic predisposition, such as rhinitis and bronchial asthma, in patients with IgG4-PD is higher than that in the general population [11]. A possible relationship between asbestos exposure and IgG4-PD as well as allergic condition has been proposed [12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hypocomplementemia, high serum IgE, and positivity for RF and ANA are often observed [11,13,14]. Various abnormal radiographic patterns, such as bronchial wall thickening, consolidation, nodule(s), ground-glass opacity, interlobular thickening, honeycombing, pleural thickening/effusion, and mediastinal lymphadenopathy, have been observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation